PENGARUH POLA ASUH DEMOKRATIS TERHADAP PERKEMBANGAN SOSIAL ANAK USIA 5-6 TAHUN - Julisnawati (Jurnal Ta'lim : Journal Ilmu Pendidikan dan Ilmu Keguruan, 2016)
This study is entitled "The Effect of Democratic Parenting on Early Childhood Social Development 5-6 Years in the Mandau River Pembina Negeri Kindergarten". The purpose of this study was to determine the effect of Democratic Parenting on Early Childhood Social Development in the Mandau River Kindergarten. In this study data were collected through the distribution of questionnaires to 56 parents of children in TK Mandina Sungai Pembina. Then do the analysis of the data obtained in the form of quantitative analysis. Quantitative analysis through t test, namely the hypothesis test in this study was used to test the significance of the influence of the independent variables on the dependent variable. The results of the analysis found that the independent variable, Democratic Parenting (X), had a positive and significant effect on Early Childhood Social Development (Y). Hypothesis testing using the t test showed that the independent variable Democratic Parenting studied was proven to significantly influence the dependent variable of social development. Then through the t test it can be seen that the significance value of 0.007 is smaller than the significant level of 0.05. Thus Ha is accepted, then Democratic Parenting has a significant effect on the Social Development of Early Childhood 5-6 Years in the Mandau River Development Kindergarten.